Plant Dvelopment Biology : Methods and Protocols - Hennig, Lars; Köhler, Claudia (New York : Humana Press, 2010)
Plants come in myriads of shapes and colors, and the beauty of plants has fascinated mankind for thousands of years. Long before Mendel discovered the laws of heritab- ity and Darwin developed his theory on evolution, the affection for ornamental plants led people to select alleles that establish novel plant forms. Today, plant developmental biology tries to discover the mechanisms that control the establishment of specialized cell types, tissues, and organs from the fertilized egg during a plant s life. Although the underlying processes of cell proliferation and differentiation are similar in plants and a- mals, plants are different because their development is usually open, and its outcome is not the faithful repetition of a general plan but is strongly in?uenced by environm- tal conditions. In the last few decades, plant developmental biology has pinpointed a large number of developmental regulators and their interactions and the mechanisms that govern plant development start to emerge. In part, this progress was enabled by the advance of powerful molecular tools for a few model species, most importantly Arabidopsis. This volume of the Methods in Molecular Biology series provides a collection of protocols for many of the common experimental approaches in plant developmental bi- ogy. All chapters are written in the same format as that used in the Methods in Molecular TM Biology series. Each chapter opens with a description of the basic theory behind the method being described.
Included bibliographical references; Index 445-448p.
Keywords: Plant Developmental biology; Botany